(untitled) (Research, Society and Development, 2022)
Institutional assessments are instruments widely used in the educational context in order to demonstrate results obtained or imminent needs for adjustments or various corrections, through the analysis of the indicators they represent. In Brazil, we have the SAEB – Basic Education Assessment System, which evaluates the education offered at primary and secondary levels, in addition to early childhood education. This is a critical analysis of the study called “Educational Assessment, SAEB and awareness of integrated high school students for their importance in the context of the Brazilian educational system”, prepared as a requirement for the completion of an academic Master’s degree at IFMT. More specifically, this work sought to present the study carried out, its difficulties and successes and critically analyze its execution. Methodologically, the research consists of applying questionnaires, in two stages that are distinguished by the intervention carried out through the use of the educational product developed. The educational product elaborated in the dissertation was a Podcast, a digital audio media tool, with low financial cost and easy and fast access. This Podcast was structured with the intention of providing students with information about the SAEB in a simple and practical way, and for its validation, a comparative analysis was carried out between the mentioned instruments applied to the study participants.